DEKONSTRUKSI DAN REKONSTRUKSI TERHADAP PENDIDIKAN KARAKTER DI MASA PANDEMI COVID 19: Strategi Pembelajaran Mata Kuliah Muamalat - Amir Bandar Abdul Majid (Risalah, Jurnal Pendidikan dan Studi Islam, 2021)
The purpose of this study is to find a learning model that can make students active and communicative in online lessons during pandemics like this. The learning model is deconstruction and reconstruction learning. This research is qualitative research that uses a descriptive approach. The form of data presentation is taken from students of the study program muamalah faculty of sharia and Islamic law Sunan Kalijaga State Islamic University Yogyakarta from Grades A, B, and C. The results obtained from this study is with the model of deconstruction and reconstruction learning that can make active learning in the sense that many students respond to the material in different points of view. The learning model can also make lecturers and students more communicative to each other.